The Effect of Non-invasive Spinal Cord Stimulation on Anorectal Function in Individuals With Spinal Cord Injury: A Case Series - Kreydin, Evgeniy; Zhong, Hui; Lavrov, Igor; Edgerton, V. Reggie; Gad, Parag (Frontiers in Neuroscience, 2022)
Spinal cord injury (SCI) is a devastating condition that impacts multiple organ systems. Neurogenic bowel dysfunction (NBD) frequently occurs after a SCI leading to reduced sensation of bowel fullness and bowel movement often leading to constipation or fecal incontinence. Spinal Neuromodulation has been proven to be a successful modality to improve sensorimotor and autonomic function in patients with spinal cord injuries. The pilot data presented here represents the first demonstration of using spinal neuromodulation to activate the anorectal regions of patients with spinal cord injuries and the acute and chronic effects of stimulation. We observed that spinal stimulation induces contractions as well as changes in sensation and pressure profiles along the length of the anorectal region. In addition, we present a case report of a patient with a SCI and the beneficial effect of spinal neuromodulation on the patient's bowel program.